Relaxation strength of localized motions in D. Sorbitol and mimicry of glass-softening thermodynamics - VIJ, JAGDISH KUMAR (American Institute of Physics, 2003)
The dielectric relaxation strength, ??JG, the relaxation rate, fm,JG and the distribution parameter, ?JG, of the faster relaxation process in D-sorbitol have been studied as a function of temperature and the cooling rate. Amongst these, fm,JG and ?JG of the glass and the supercooled liquid change smoothly with the temperature, T, but ??JG of the glassy state increases slowly on heating until the glass-softening range is reached and thereafter it increases rapidly at T above the glass-softening temperature, Tg. Thus its plot against T has an elbow-shape, remarkably similar to that observed for the volume, enthalpy and entropy. The derivative (d??JG/dT) increases relatively abruptly at Tg like the thermal expansion coefficient and the heat capacity of a glass. Thus ??JG is a function of the state?s entropy and volume. The distribution of relaxation times became narrower as T was increased, and fm,JG increased according to the Arrhenius equation, fm,JG = 2.992?1014?exp[?5.312?104/RT], where R = 8.314?J?(K?mol)?1. It is deduced that fm,JG increases on structural relaxation of D-sorbitol. The results indicate that the relaxation mechanism involves motions of segments of the D-sorbitol molecules or of the whole molecule in local regions.
PUBLISHED
Keywords: Electronic & Electrical Engineering